A pre-experimental design evaluation of brief harm reduction interventions to improve coping self-efficacy of carers of people with substance use disorder - Ilze Swanepoel; Gretel Crafford; Stephan Geyer; Tessa S. Marcus (Harm Reduction Journal, 2023)
Abstract Background Globally, the rise in the number of people living with a substance use disorder (SUD) carries a multitude of individual and social health implications for carers and their families, often impacting negatively on their quality of life. Considered from a harm reduction approach, SUD is understood as a chronic protracted, complex health and social condition. From the extant literature, there is no evidence of the harm reduction approach being applied to address the needs of carers/family members who carry the burden of SUD care. This study preliminarily evaluated the Care4Carers Programme. It is a purposively designed set of brief interventions to improve the coping self-efficacy of carers of people with SUD (PwSUD carers) by equipping them to think about ways to exert control over their motivation, behaviours and social environment. Methods A pre-experimental, one group pretest–posttest design was implemented with 15 purposively selected participants in the Gauteng Province of South Africa. The intervention was conducted by the lead researcher, a registered social worker. Eight brief intervention sessions were held, over 5–6 weeks at research sites where the participants were identified. The coping self-efficacy scale was completed before and directly after exposure to the programme. Results were analysed using paired t-tests. Results There were statistically significant (p < .05) improvements in carers’ coping self-efficacy, both overall and in respect of each of its constituent components: problem-focused coping, emotion-focused coping and social support strategies. Conclusions The Care4Carers Programme improved the coping self-efficacy of carers of people living with SUDs. The application of this programmatic harm reduction intervention to support PwSUD carers should be tested on a larger scale across South Africa.